Pengaruh Motivasi Kerja dan Pemanfaatan Teknologi Informasi Terhadap Kinerja Petani Sleman Yogyakarta - Rifqi Syarif Nasrulloh; Khoirul Hikmah; Arief Subyantoro (Publikasi Indonesia, 2022)
This study aims to re-confirm the effect of work motivation and the use of information technology on individual performance based on previous research with different research objects. The population in this study are all farmers who are registered as members of farmer groups in each region. The sampling technique was accidental sampling method and obtained 102 farmer respondents who filled out the questionnaire. The results indicate that this study supports previous findings which state that 1) work motivation has a positive impact on farmer performance, 2) the use of information technology has a positive impact on farmer performance. By building self-motivation through rewards that are expected to be adjusted to personal goals so that individual performance will increase because of the motivation for personal goals that they already want to get. Meanwhile, the use of technology develops individual performance by looking at the frequency of use of information technology which is more dominant than other indicators of the use of technology.